Design rules for time of flight Positron Emission Tomography (ToF-PET) heterostructure radiation detectors. Issue 6 (June 2022) - Krause, Philip; Rogers, Edith; Birowosuto, Muhammad Danang; Pei, Qibing; Auffray, Etiennette; Vasil'ev, Andrey N.; Bizarri, Gregory
Abstract: Despite the clinical acceptance of ToF-PET, there is still a gap between the technology's performance and the end-user's needs. Core to bridging this gap is the ability to develop radiation detectors combining a short attenuation length and a sub-nanosecond time response. Currently, the detector of choice, Lu2 SiO5 :Ce 3+ single crystal, is not selected for its ability to answer the performance needs, but as a trade-off between requirements and availability. To bypass the current performance limitations, in particular restricted time response, the concept of the heterostructured detector has been proposed. The concept aims at splitting the scintillation mechanisms across two materials, one acting primarily as an absorber and one as an ultra-fast emitter. If the concept has attracted the interest of the medical and material communities, little has been shown in terms of the benefits/limitations of the approach. Based on Monte Carlo simulations, we present a survey of heterostructure performance versus detector design. The data allow for a clear understanding of the design/performance relationship. This, in turn, enables the establishment of design rules toward the development and optimization of heterostructured detectors that could supersede the current detector technology in the medical imaging field but also across multiple sectors (e.g. high-energy physics, security). Abstract : Heterostructured radiation detector; Ultra-fast timing; Positron Emission tomography